Teaching technologies through intersubject ties (Pedagogy of Higher and Secondary Education, 2014)
Nedashkovsky Y. V., Kuchma А. I. Teaching technologies through intersubject ties.The article gives some aspects of preparing handicraft teachers with regard to using intersubject ties and computer technologies
Keywords: computer technologies; electrotechnical disciplines; intersubject knowledge; teaching technologies